2011
DOI: 10.1007/s11269-011-9822-1
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Assessment of the Mudurnu River, Turkey, Using Biotic Indices

Abstract: In this study, the effect of domestic and industrial pollutants on the water quality of Mudurnu River was searched. Water and benthic macroinvertebrate samples were taken from five stations selected on Mudurnu River during 12 months (2006)(2007). COD (Chemical Oxygen Demand), BOD (Biochemical Oxygen Demand), TKN (Total Kjeldahl Nitrogen), NO − 3 -N (Nitrate-Nitrogen), PO −3 4 -P (Phosphate-Phosphorous), NH + 4 -N (Ammonium-Nitrogen), Phenol data and scores of BMWP (Biological Monitoring Working Party) score sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
3
16
0
1
Order By: Relevance
“…(), Alba‐Tercedor et al . (), Czerniawska‐Kusza () or Ogleni and Topal (), being appropriate mechanisms to measure the freshwater quality. However, although our results agree with previous studies, it should be taken into account the low number of available data for the correlation analysis in some typologies.…”
Section: Discussionmentioning
confidence: 97%
“…(), Alba‐Tercedor et al . (), Czerniawska‐Kusza () or Ogleni and Topal (), being appropriate mechanisms to measure the freshwater quality. However, although our results agree with previous studies, it should be taken into account the low number of available data for the correlation analysis in some typologies.…”
Section: Discussionmentioning
confidence: 97%
“…It is seen in the relevant literature that the various versions of the BMWP and ASPT indices have been used to determine water quality in streams, and the results have been compared by researchers (Ferreira et al, 2004;Czerniawska-Kusza, 2005;Roche et al, 2010;Ogleni and Topal, 2011;Kazancı et al, 2013;Lewin et al, 2013). Therefore, in the present study, following the applications in the literature, examining all versions of the BMWP suggested that the second station was slightly polluted; the other stations seemed to have good water quality, or were at least unpolluted.…”
Section: Discussionmentioning
confidence: 99%
“…This family was found in Thailand with concentrations of BOD 5 , DO and conductivity of 7 mg·L −1 , 1.1 mg·L −1 and 377 µS·cm −1 respectively. In Ghana, these taxa were present with a BOD 5 of 2 mg·L −1 , DO of 4.1 mg·L −1 and a conductivity of 1250 µS·cm −1 [10], while in Turkey, Baetidae were found when BOD 5 was 8.8 mg·L −1 [49].…”
Section: Analysis Of the Chosen Ept Taxa In Relation With The Bmwp-colmentioning
confidence: 98%